Enhancement of Corrosion Resistance in Fly Ash Blended Cement Concrete using Organic Inhibitors - Rajkumar, V.; Kannan, K.; Sundararajan, R. (Asian Journal of Chemistry, 2011)
This paper presents the results of experimental investigations that were carried out to study the strength, micro structural and corrosion resistance characteristics of 30 % fly ash blended cement concrete with 3 % addition of organic inhibitors namely diethanolamine, benzimidazole, triethanolamine, triethylamine as corrosion inhibiting admixtures. The specimens were tested for compressive strength, split tensile strength, flexural strength, bond strength and water absorption test to ascertain their mechanical characteristics. The resistance to corrosion is evaluated based on the performance of the concrete for the penetration of chloride ions by means of impressed current technique. The possibilities of removal of chloride electrochemically and studies on migration of inhibitor were established. From the results obtained, it is found that the fly ash blended cement concrete increases the strength, reduces the permeability by the pozzolonic reaction and increases the durability of concrete with the addition of inhibitors. It offers good resistance against chemical attack and increases corrosion resistance in addition to increase in overall properties of concrete.